Effect of Diabetes Mellitus Educational Video on Knowledge Improvement among Adolescents in Indonesia - Puspita, Listya; Mlwale, Husna Juma; Nurjannah (Vocational: Journal of Educational Technology, 2025)
Diabetes Mellitus is a health problem that can be prevented by increasing knowledge during adolescence. However, the lack of understanding about this disease among adolescents hinders early prevention efforts. This study aims to examine the effect of educational video media about Diabetes Mellitus on improving adolescents’ knowledge. A pre-experimental design with a one-group pretest-posttest approach was used. The research sample consisted of 42 students from Bina Cipta Senior High School (SMA) Palembang, selected using purposive sampling. The intervention involved showing an educational video on Diabetes Mellitus after the pretest, followed by a posttest to measure knowledge changes. The T-test results showed a significant value of 0.000 (p<0.05), indicating a significant increase in knowledge after the video intervention. The findings imply that educational videos are an effective tool to enhance adolescent knowledge about Diabetes Mellitus and can be used as an alternative method in health promotion strategies within schools to address knowledge gaps and support early disease prevention.